A study on expression of programmed death ligand-1 in small cell lung carcinoma and correlation with clinicopathological parameters - Sudha, Sudha; Shukla, Saumya; Husain, Nuzhat; Kumar, Hemant; Pandey, Rahul Kumar; Kant, Surya (Polish Journal of Pathology, 2024)
Small cell lung carcinoma (SCLC) is characterized by rapid growth and an aggressive clinical course. Standard therapy regimes have limited effects on disease course; therefore the prognosis of SCLC is poor. In the current study, the frequency of programmed death ligand 1 (PD-L1) expression in SCLC and its correlation with clinico-pathological features were evaluated. The study included 100 cases of SCLC wherein testing for PD-L1 was done with the SP263 clone on the Ventana benchmark XT system. Cases with > 1% PD-L1 expression in tumour cells or immune cells were categorized as positive. PD-L1 expression was identified in 14% of cases using the cut-off of ≥ 1%. The tumour proportion score was 10% and the immune proportion score was 9.78% using a cut-off of ≥ 1%. PD-L1 positive expression was more frequent in the male population with age > 40 years. All the patients with positive PD-L1 expression were smokers. In the PD-L1 positive group, presence of necrosis was identified in 71.4% of cases and when compared with the PD-L1 negative subgroup this finding was statistically significant (p = 0.010). Personalized targeted therapy for cases of SCLC is still under evaluation. The use of immunotherapeutic targets, such as PD-L1, may help to define a new treatment strategy for SCLC. Development of new treatment strategies may improve prognosis and survival.